1974
DOI: 10.1007/bf01221628
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the amelioration of the characteristics of New Zealand Obese (NZO) mice following implantation of islets of Langerhans

Abstract: Summary. New Zealand Obese (NZO) mice are eharaeterised by hyperglyeaemia, hyperinsulinaemia and obesity. The blood glucose and plasma insulin levels of these mice can be lowered to levels approaching those normally associated with non-obese mice, by the intraperitoneal implantation of pancreatic islets from albino mice which have had their fl-cells selectively destroyed by streptozotocin. Removal of these implanted islets causes the animals to revert to their original state. It would seem, therefore, that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Although earlier studies suggested a possible defect in the development of pancreatic peptide-positive (PP) cells in the islets of NZO/Wehi mice (Gates and Lazarus, 1977;Gates et al, 1972Gates et al, , 1974, we observed numerous granulated PP-cells, as well as glucagoncontaining alpha cells. Although less numerous, somatostain containing delta cells were also demonstrable by immunochemical staining (Fig.…”
Section: Junger Et Alcontrasting
confidence: 92%
See 1 more Smart Citation
“…Although earlier studies suggested a possible defect in the development of pancreatic peptide-positive (PP) cells in the islets of NZO/Wehi mice (Gates and Lazarus, 1977;Gates et al, 1972Gates et al, , 1974, we observed numerous granulated PP-cells, as well as glucagoncontaining alpha cells. Although less numerous, somatostain containing delta cells were also demonstrable by immunochemical staining (Fig.…”
Section: Junger Et Alcontrasting
confidence: 92%
“…Genetic segregation analysis conducted to locate NZO-contributed diabetogenic loci failed to identify its H2 z haplotype, associated with lupus and glomerulonephritis in (NZB ϫ NZW) F1 mice (Hirose et al, 1983), as a diabetogenic contributor, as might be anticipated if T cell autoimmunity were a primary event. The fact that NZO mice express the H2 z haplotype casts doubt on earlier reports that transplantation of C57BL/6J (H2 b ) islets into diabetic NZO recipients "cured" the diabetes (Gates et al, 1972(Gates et al, , 1974). An alloimmune rejection would be anticipated across this major histocompatibility barrier.…”
Section: Junger Et Almentioning
confidence: 98%
“…We postulated that a factor was being secreted by the implanted mouse islets and that this factor was responsible for the reversion process (2). At least four hormones are present in islets of Langerhans.…”
Section: Introductionmentioning
confidence: 99%
“…The intraperitoneal implantation into New Zealand obese (NZO) mice of albino mouse islets encased in Millipore bags, causes the hyperinsulinaemia, hyperglycaemia, lag glucose tolerance and body weight gain of the implanted mice to return to normal (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Barker et al [82] found that after transplantation of rat islets to immunosuppressed NZO mice glucose tolerance test results returned to normal. Normal islets may produce a factor that decreases insulin resistance and alleviates the syndrome [189].…”
Section: Islet Transplantation On Natural Models Of Diabetesmentioning
confidence: 99%